(untitled) (Homoeopathy for All, 2026)
Background: Schizophrenia is a severe, chronic psychiatric disorder characterized by disturbances in thought, perception, emotion, and behavior. It affects social functioning, occupational performance, and overall quality of life. Conventional antipsychotic therapies primarily target symptom suppression and are often associated with significant adverse effects, poor compliance, and incomplete functional recovery. Homoeopathy, through its individualized and holistic approach, aims to restore mental and emotional balance by addressing theunderlying disturbance of the vital force. Objective: To review available literature and clinical evidence regarding the role of homoeopathic medicines in the management of schizophrenia, with particular emphasis on cognitive, emotional, behavioral, and functional outcomes. Methods: A comprehensive review of published literature including clinical studies, case reports, observational studies, and homoeopathic materia medica was conducted. Databases, homoeopathic journals, textbooks, and institutional publications related to schizophrenia and psychotic disorders were analyzed to identify therapeutic trends and commonly indicated remedies. Results: Homoeopathic medicines such as Anacardium orientale, Stramonium, Hyoscyamus niger, Sulphur, Natrum muriaticum, and Lycopodium clavatum have demonstrated beneficial effects in reducing hallucinations, delusions, emotional instability, social withdrawal, and cognitive disturbances. Reports indicate improvement in insight, sleep patterns, emotional regulation, and daily functioning. No serious adverse effects were reported. Conclusion: Homoeopathy appears to be a promising complementary therapeutic modality in schizophrenia, offering individualized treatment that addresses both psychotic symptoms and emotional well-being. While existing evidence is encouraging, large-scale randomized controlled trials are required to establish definitive efficacy and explore neurobiological mechanisms.